Modern herbal medicines in the treatment of acute rhinosinusitis - S. A. Artyushkin; S. V. Ryazantsev; N. V. Eremina; S. A. Eremin (Медицинский совет, 2018)
Acute rhinitis (ICD-X, acute nasopharyngitis, runny nose – J00) and acute sinusitis (J01) make up a larger proportion of all acute upper respiratory tract diseases (J00-J06). The prescription of antibacterial drugs for the treatment of virus diseases in the ENT area and the unproven or unconfirmed bacterial disease is considered erroneous and dangerous. In this regard, the role of pathogenetically justified therapy in the treatment of ARS increases. When choosing the medicines for ARS, particular attention is given to the use of herbal medicines with combination effect, which found its way into legislation – a group of herbal medicines is included in the list of ARS treatment medicines in adults in the EPOS-2012 document, and methodological recommendations approved by the National Medical Association of Otorhinolaryngologists.